Proteomic characterization of human proinflammatory M1 and anti‐inflammatory M2 macrophages and their response to Candida albicans. Issue 12 (22nd May 2014) - Reales‐Calderón, Jose Antonio; Aguilera‐Montilla, Noemí; Corbí, Ángel Luis; Molero, Gloria; Gil, Concha
<x xml:space="preserve">Abstract</x> In response to different stimuli, macrophages can differentiate into either a pro‐inflammatory subtype (M1, classically activated macrophages) or acquire an anti‐inflammatory phenotype (M2, alternatively activated macrophages). Candida albicans is the most important opportunistic fungus in nosocomial infections, and it is contended by neutrophils and macrophages during the first steps of the invasive infection. Murine macrophages responses to C. albicans have been widely studied, whereas the responses of human‐polarized macrophages remain less characterized. In this study, we have characterized the proteomic differences between human M1‐ and M2‐polarized macrophages, both in basal conditions and in response to C. albicans, by quantitative proteomics (2DE). This proteomic approach allowed us to identify metabolic routes and cytoskeletal rearrangement components that are the most relevant differences between M1 and M2 macrophages. The analysis has revealed fructose‐1, 6‐bisphosphatase 1, a critical enzyme in gluconeogenesis, up‐regulated in M1, as a novel protein marker for macrophage polarization. Regarding the response to C. albicans, an M1‐to‐M2 switch in polarization was observed. This M1‐to‐M2 switch might contribute to Candida pathogenicity by decreasing the generation of specific immune responses, thus enhancing fungal survival and colonization, or instead, may be part of the host attempt to reduce the inflammation and limit the damage of the infection.